2021
DOI: 10.1108/etpc-03-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

“Wearing Only Our Skin”: the multimodal literacies classroom as a living arrangement

Abstract: Purpose Literacy research exploring multimodal composition and justice-oriented children’s literature each have rich landscapes and histories. This paper aims to add to both of these bodies of scholarship through the emerging assemblage of Studio F, a fifth-grade classroom. The authors share poststructural analytic encounters with attention to the unexpected multimodal relationships and the justice-oriented talk and texts that emerged, as well as the classroom conditions that produce them. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Due to the limited class time, teachers can only teach the vocabulary in the textbook, and it is far from enough for students to learn vocabulary only by class time, so it is necessary to use suitable teaching methods or efficient media tools to make up for this deficiency. Figure 3 Results of the investigation on the application effect of multimedia technology in reading teaching According to the survey results in Figure 3, 75% of teachers still believe that multimedia technology has a positive effect on reading teaching [12] . However, there are also a few teachers think that the function of multimedia has not reached their ideal effect, which shows that there are also shortcomings and deficiencies in the process of using multimedia, this requires teachers to strengthen the practicability of multimedia technology and timely communicate with students.…”
Section: Figure 2 Results Of the Survey On The Influence Of English R...mentioning
confidence: 99%
“…Due to the limited class time, teachers can only teach the vocabulary in the textbook, and it is far from enough for students to learn vocabulary only by class time, so it is necessary to use suitable teaching methods or efficient media tools to make up for this deficiency. Figure 3 Results of the investigation on the application effect of multimedia technology in reading teaching According to the survey results in Figure 3, 75% of teachers still believe that multimedia technology has a positive effect on reading teaching [12] . However, there are also a few teachers think that the function of multimedia has not reached their ideal effect, which shows that there are also shortcomings and deficiencies in the process of using multimedia, this requires teachers to strengthen the practicability of multimedia technology and timely communicate with students.…”
Section: Figure 2 Results Of the Survey On The Influence Of English R...mentioning
confidence: 99%
“…In Wendy's fifth‐grade classroom, we (Zapata & Kleekamp, 2021) similarly found that curating students' access to justice‐oriented picturebooks through opera was an experience that was saturated with affect and embodied literacies that launched students into critical literature encounters. When composing an opera in response to justice‐oriented picturebooks, students composed arias and staged their bodies and instruments as they interrogated instances of race and racism in the narrative.…”
Section: Animating Critical and Aesthetic Experiences With Picturebooksmentioning
confidence: 96%
“…In addition to mediating racial healing in the context of teachers' critical curation, picturebooks can be responded to through writing, art, play, or drama, to expand aesthetic responses where personal, affectual, embodied, critical meanings can take shape. (Wissman, in press for 2022; Zapata & Kleekamp, 2021). Curating affectual and embodied critical picturebook encounters invite children to express their aesthetic responses—and use their bodies and voice—to do so in ways that resist marginalization and racial prejudice.…”
Section: Animating Critical and Aesthetic Experiences With Picturebooksmentioning
confidence: 99%
“…It is in this sense that vibrancy is seen in the entanglements that make up literacy in classroom encounters, part of which is embodied talk and action. Part of these entanglements are also discourses that not only shape literacy but also (re)produce asymmetries as they erase or other particular student bodies, especially ones from non‐dominant cultures (Beucher et al, 2019; Zapata & Kleekamp, 2021). In this view, children's and teachers' bodies are read as being entangled both with material and discourse; and literacy becomes what matters as people, things, sounds, modalities, and meanings come together in classrooms (Zapata & Kleekamp, 2021).…”
Section: Talk Discourse and Noise In Schooled Bodiesmentioning
confidence: 99%